(untitled) (Journal of Economic Research & Business Administration, 2018)
The aim of this study is to determine and compare the food safety knowledge, attitude and behavior of Employees in 4-5 star hotels in Kazakhstan, and to investigate the effects of these determinants on each other. For this purpose, a survey is performed with 256 employees who work for different positions in the hotel. The collected data is analyzed by using descriptive statistics and structural equation modeling. As a result, it is determined that food safety knowledge has not a significant influence on food safety behavior. However, there is a high correlation between food safety attitude and behavior, and a medium correlation between food safety knowledge and attitude. Consequently, training, profession and experience of the employee are very important factors to be paid attention for ensuring food safety in enterprises. Thus, it is necessary to determine the training needs of the employee, and to provide training and seminars taking into account the position of each employee in the hotel.